The epidemiology of melioidosis in Ubon Ratchatani, northeast Thailand. - Suputtamongkol, Y; Hall, A; Dance, D; Chaowagul, W; Rajchanuvong, A; Smith, MD; White, N (1994)
BACKGROUND: Melioidosis, or infection with Pseudomonas pseudomallei is an important cause of morbidity and mortality in South East Asia and Northern Australia. The epidemiology of melioidosis in Ubon Ratchatani, Northeast Thailand was studied over a 5-year period from 1987 to 1991. METHODS: Rates and, when possible, the risks of developing melioidosis were calculated. The numerator was the number of culture-proven cases of melioidosis seen in the 1000-bed referral hospital of the province. The denominators were obtained from the population census, a survey of Health, Welfare and Use of Traditional Medicine, and the North Eastern Meterological Centre, Thailand. RESULTS: The average incidence of human melioidosis was 4.4 (95% confidence interval [CI]: 3.8-5.0) per 100,000. The disease affected all ages with the highest incidence in 40-60 years olds. Melioidosis was 1.4 (95% CI: 0.4-5.3) times more common in males than females. The disease showed a significant seasonal variation in incidence, and a strong linear correlation with rainfall (r = 0.7, 95% CI: 0.5-0.9) Adults exposed to soil and water in their work (most were rice farmers) had an increased risk of melioidosis (in the 40-59 year age group, relative risk = 4.1, 95% CI: 2.4-6.9). Most adult patients had an underlying disease (mainly diabetes mellitus) predisposing them to this infection. CONCLUSION: Melioidosis may result from either acute exposure to the organism in the soil and water, or 're-activation' of an asymptomatic childhood infection (by an unidentified possibly infective seasonal cofactor). The results from this analysis are consistent with both hypotheses. Further epidemiological studies are needed to identify risk factors so that optimal strategies for control of melioidosis may be developed.